A 187Re-187Os, 87Rb-86Sr, highly siderophile and incompatible trace element study of some carbonaceous, ordinary and enstatite chondrite meteorites. (1st February 2022) - Phelan, Nicole; Day, James M.D.; Dhaliwal, Jasmeet K.; Liu, Yang; Corder, Christopher A.; Strom, Caleb; Pringle, Emily; Assayag, Nelly; Cartigny, Pierre; Marti, Kurt; Moynier, Frédéric
Abstract: New 187 Re- 187 Os, 87 Rb- 87 Sr, triple O-isotope isotope, bulk rock highly siderophile- (HSE: Os, Ir, Ru, Pt, Pd, Re), major- and trace-element abundance data are reported for a variety of carbonaceous, ordinary and enstatite chondrite meteorites. In addition, new mineral chemical data are reported for the Chelyabinsk LL5 ordinary chondrite fall for comparison with existing chondrite data and to investigate element sequestration into metal and mineral phases within some chondrites. The focus of the study is to link the variations observed in the HSE abundances and Re-Os isotopes with other isotopic and elemental data to explore the relative roles of sample sizes, terrestrial alteration and parent body processes more fully on chondrite meteorite compositions. Trace element variations in Chelyabinsk silicate, oxide and metal grains highlight the importance of geochemical heterogeneity imparted by mineralogical variations and mode effects, as well as sample size. Using a range of sample powder aliquot sizes, it is possible to show that this becomes significant for the HSE at <0.1 g. Variations in high field strength elements relative abundances (HFSE: Ti, Zr, Nb, Ta, Hf) are also identified within individual aliquots of carbonaceous chondrite Ivuna, emphasizing the importance of complete dissolution of refractory phases. The range of fall and find meteorites examined here demonstrates that terrestrial alteration effects revealed for trace elements (e.g., Ba, U, Sr) do not correlate particularly well with Re/Os variations. Instead, the Re/Os ratios of carbonaceous chondrites are susceptible to disturbance, more so than indicated by incompatible trace element systematics, with the Murchison CM2 carbonaceous chondrite showing significant Re/Os fractionation between sample aliquots. For sample aliquots measured that do not show significant mode or terrestrial alteration effects, parent body processes appear to be largely restricted to thermal metamorphism and dehydration. Including data for this study, the combined published dataset for Re-Os isotope and HSE abundances now extends to 33 ordinary, 39 carbonaceous, 27 enstatite and 6 Rumuruti chondrites. The range in absolute HSE abundances among these meteorite groups is ∼30%, with all chondrites having, within uncertainties, the same average Os, Ir, Ru, Pt and Pd abundances. Notably, carbonaceous chondrites have long-term Re/Os ∼ 8% lower than for the other chondrite groups. If chondrite groups are representative of early planetary feedstocks, then the measured 187 Os/ 188 Os of ordinary chondrites make them a close match to the composition of the bulk silicate Earth. Assuming ∼0.5% late accretion of ordinary chondrites to Earth, this would result in a long-term Rb/Sr ratio ∼0.6% higher than from late accretion of carbonaceous chondrites, indicating that ordinary chondrites are a potentially attractive source for moderately volatile enrichment.